Problem solving ability based on Newman procedure in Team Games Tournament learning - Alhara, Zepta Habib; Asikin, Mohammad; Amidi, Amidi (Unnes Journal of Mathematics Education, 2021)
The purpose of this research were to describe about how was the learning quality of Team Games Tournament (TGT) in students' mathematical problem solving abilities, and to describe about how were students' problem solving abilities based on Newman's procedures. The research method used was a mixed method where students are subjected to TGT learning models. The population used in this study were students of class VIII in one of junior high school in Pekalongan in the even semester of the 2018/2019 academic year distributed in four classes and the sample used was class VIIIC. The subjects in this study was selected by using purposive sampling techniques with consideration that the selected subjects can represent each category of mathematical problem solving abilities. Based on the results of the analysis, it can be concluded that learning process of TGT that have been conducted in the research class is in accordance with the lesson plan and other support devices or tools that has been made by researchers. Based on observations made by the observer, the criteria obtained for students and teacher activities were very good. The average learning outcomes of class VIIIC students that were subjected to TGT learning model in students' mathematical problem solving abilities have reached mastery learning. Research subjects that have high problem solving ability generally know the location and cause of the error when working on a problem, research subjects that have problem solving ability are partially aware of the location and cause of the error when working on a problem, and research subjects who have low problem solving ability generally do not know the location and cause of the error when working on a problem.